Ablation of Intrahepatic Cholangiocarcinoma - Sweeney, Jennifer; Parikh, Nainesh; El-Haddad, Ghassan; Kis, Bela (Seminars in Interventional Radiology, 2019)
Intrahepatic cholangiocarcinoma is the second most common primary liver cancer but represents only a small portion of all primary liver cancers. At the time of diagnosis, patients are often not surgical candidates due to tumor burden of other comorbidities. In addition, there is a very high rate of tumor recurrence after resection. Local regional therapies, specifically ablative therapies of radiofrequency ablation, microwave ablation, cryoablation, and irreversible electroporation, have proven to be beneficial with other hepatic tumors. The purpose of this review is to provide an overview and update of the medical literature demonstrating ablative therapy as a treatment option for intrahepatic cholangiocarcinoma.
Keywords: intrahepatic cholangiocarcinoma; microwave ablation; radiofrequency ablation; cryoablation